A postcard illustrating the church of Albert in Somme with t - Auteur inconnu (Wikimedia Commons)
Notice image issue de Wikimedia Commons. Titre: A postcard illustrating the church of Albert in Somme with t. A postcard illustrating the church of Albert in Somme with the church tower in the form of the Virgin crashing to the ground. Process print Iconographic Collections Keywords: Mary | Eglise d'Albert (Somme, France)
Droits : Licence CC BY 4.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; architecture; histoire locale; église; Carte postale